Alcohol and drug abuse in post-conflict Iraq - Al-Hemiary, Nesif J.; Hashim, Mushtaq T.; Al-Diwan, Jawad K.; Razzaq, Emad Abdul (Journal of the Faculty of Medicine Baghdad, 2016)
Background: The 2006-2007 Iraqi Mental Health survey (IMHS) reported surprisingly low prevalence of alcohol and drug abuse in the Iraqi population. Since then anecdotal and clinical reports have suggested that abuse of alcohol and drugs in Iraq has increased. To investigate this possibility, we conducted a survey of drug and drug abuse at youth centers in Baghdad. Objective: To investigate this possibility, we conducted a survey of drug and drug abuse at youth centers in Baghdad. Patients and methods: A total of 2678 persons were included in this survey with male to female ratio of 3.8:1. They were randomly selected from youth centers located in different sectors in Baghdad (Sader city, Al-Rusafa side and Al-Karkh side). Composite International Diagnostic Interview was used to generate diagnosis. The interviewers were youth center staff who were trained by psychiatrists. Demographic data, age of onset and crowding index were obtained. Data collection was carried out on Dec. 2009. Results: A total of 16.7% met criteria for alcohol abuse and 7.02% met criteria for drug abuse. In those below 18 years of age, 2.1% reported alcohol abuse and 1.1% reported drug abuse. The peak age for alcohol and drug abuse was at 24-35 years. No female reported alcohol and substance abuse. The age of onset of alcohol was 21.7 ± 3.6 years and for drug abuse was 22 ± 5.8 years. Alcohol abuse was significantly associated with high crowding index, but drug abuse was not associated with crowding index. Low educational level was associated significantly with both alcohol and drug abuse. Conclusion: High rates of alcohol and drug abuse were recorded. A tendency for early age of onset in alcohol and drugs was observed. High household density and low educational level are important factors in alcohol and drug abuse.